EVALUASI PROGRAM PINJAMAN BERGULIR PNPM MANDIRI PERKOTAAN KEPADA MASYARAKAT MISKIN KELURAHAN TIDAR UTARA KECAMATAN MAGELANG SELATAN KOTA MAGELANG TAHUN 2011-2012 - Dwi Ratna Cahyaningtyas; Kushandajani .; Puji Astuti (Journal of Politic and Government Studies, 2014)
AbstractDevelopment programs implemented in Indonesia aimed to give greater attention to poverty alleviation efforts. One such program is the Revolving Loan Program PNPM Urban. Sub-District of Magelang District of Southern North Tidar including one of the areas subject to the PNPM Urban. It is interesting to study because it can be said that the Village is one of the areas in the district of South Magelang failure Revolving Loan Program PNPM Urban start of 2011 to February 2014 with the 0 % rate of return and the level of congestion reaches 100 %.The research method used in this research is descriptive qualitative research method. The purpose of the research is done by using the theory rogram evaluation according to Bridgman and Davis. Sources of data in this study was obtained from interviews with sources and records or documents related to the study. Data collection techniques is by interview, observation, and documentation. Data analysis techniques with data reduction, data display and conclusion.Basically failure Revolving Loan Program PNPM Urban Village in North Tidar of them influenced by the mindset of the population should differ from the rural population. But society in general more individual selfish and do not have an attitude of indifference. This can be reflected not only on the members of self-help groups (KSM) alone but also of good managers management of CommunitySelf-Reliance Agency (BKM), Financial Management Unit (UPK) and facilitatorswho are less focused on job performance is influenced by the other principal.Fixing a healthy communication systems can provide synergies betweeninstitutions that are able to run better in the future.Keywords: Evaluation Program, Revolving Loan, Village North Tidar